2021
DOI: 10.3390/chemengineering5040066
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Dynamic Modeling Approach to Simulate a Segmented Distillation Column for Flexible Operation

Abstract: The need for flexible process equipment has increased over the past decade in the chemical industry. However, process equipment such as distillation columns have limitations that significantly restrict flexible operation. We investigate a segmented tray column designed to allow flexible operation. The design consists of radial trays connected at the downcomer of each tray. Each segment can be operated separately, but depending on the capacity of the feed stream, additional segments can be activated or deactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…As single segments of this new tray design can be operated individually, these segments can be started‐up or shut‐down to widen or shorten the operating window as needed. Moreover, previous simulative studies by Bruns et al [ 3 ] have shown, that by transferring liquid from an active segment to an adjacent segment, the start‐up time can be reduced significantly, leading to shorter response times during operation. For this new tray design two types of operation were defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As single segments of this new tray design can be operated individually, these segments can be started‐up or shut‐down to widen or shorten the operating window as needed. Moreover, previous simulative studies by Bruns et al [ 3 ] have shown, that by transferring liquid from an active segment to an adjacent segment, the start‐up time can be reduced significantly, leading to shorter response times during operation. For this new tray design two types of operation were defined.…”
Section: Discussionmentioning
confidence: 99%
“…Transferring liquid from a segment operating at steady‐state conditions to an adjacent segment to be started‐up accelerates the formation of temperature and concentration profiles during start‐up operation. Previous simulation studies performed by Bruns et al [ 3 ] have shown that by transferring liquid phase on every tray from the segment operated at steady‐state to the adjacent started‐up segment, start‐up times can be reduced by up to 90%. This in turn leads to faster response times during flexible operation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the installation of buffer tanks can help to reduce the loss of valuable material. Further measures described by Riese et al are aiming at an internal structuring of the column to enhance capacity flexibility 113 and reduce start‐up times 114 . The internal segmentation of the column enables the independent operation of singular segments and, due to the proposed column design, 115 a start‐up of adjacent segments by pre‐defined concentration and temperature profiles.…”
Section: Literature Review On Dsm Options In Biofuel Production Plantsmentioning
confidence: 99%
“…Further measures described by Riese et al are aiming at an internal structuring of the column to enhance capacity flexibility 113 and reduce start-up times. 114 The internal segmentation of the column enables the independent operation of singular segments and, due to the proposed column design, 115 a start-up of adjacent segments by pre-defined concentration and temperature profiles. This design approach leads to an increase in FOL from 50% to 120% and a reduction of start-up time of >90%.…”
Section: Distillationmentioning
confidence: 99%
“…The modeling and control of a distillation column in a petroleum process are presented in [ 3 ]. The simulation of a segmented distillation column in flexible operation considering dynamic modeling is developed in [ 4 ]. The modeling and simulation of a batch reactive distillation column with optimization effects are proposed in [ 5 ].…”
Section: Introductionmentioning
confidence: 99%